Characterization of a dense medium plasma reactor for naval wastewater treatment and the development of a tubular high-density plasma reactor - Johnson, Derek C., author; Dandy, David S., advisor (Colorado State University. Libraries, 2006)
Plasma treatment of contaminated water appears to be a promising alternative for the oxidation of aqueous organic pollutants. This study examines the kinetic and oxidation mechanisms of methyl t-butyl ether (MTBE) in a dense medium plasma reactor (DMPR) utilizing gas chromatography-mass spectrometry and gas chromatography-thermal conductivity techniques. A rate law is developed for the removal of MTBE from an aqueous solution in the DMPR. Rate constants are also derived for three reactor configurations and two pin array spin rates. The oxidation products from the treatment of MTBE contaminated water in the DMPR were found to be predominately carbon dioxide, with smaller amounts of acetone, t-butyl formate and formaldehyde. The lack of stable intermediate products suggests that the MTBE is, to some extent, oxidized directly to carbon dioxide, making the DMPR a promising tool in the future remediation of water. Chemical and physical mechanisms, together with carbon balances, are used to describe the formation of the oxidation products and the important aspects of the plasma discharge. Computational fluid dynamics is applied to the study of 3D fluid flow in a DMPR under different operating conditions. Reaction mechanisms and rates for the removal of MTBE in a DMPR are developed from experimental data to determine the plasma volume, the rate of interphase mass transfer and the photolysis rate of MTBE via UV emission from the plasma. The simulations show that, in the DMPR, the volume of fluid in contact with the plasma only constitutes a maximum of approximately 10% of the fluid passing through the recirculation channels. The simulations also predict large pressure gradients on the pin electrode tips, resulting in a small discharge area located away from the region in which the radius of curvature is minimized. This result has been confirmed experimentally in the fact that it is observed that the pin electrodes sputter metal from an area of similar size and location to the low-pressure region predicted by the simulations. The chemical kinetics developed in this study are incorporated into the simulation to model the attenuation of MTBE in the DMPR. Fluid volumes are assigned the appropriate reaction mechanism and corresponding reaction rates. The simulation results accurately capture the experimental observations in that the MTBE concentration is reduced to approximately 5% of its original value in 11 min. Although only a small fraction of the fluid interacts with the plasma, oxidation due to the plasma is shown to be the major loss mechanism. Experiments have yielded a number of important insights into the energy distribution, sparging and oxidation of MTBE, benzene, ethylbenzene, toluene, m- and p-xylene, and o-xylene (BTEX) in a DMPR. It has been found that the DMPR transferred a relatively small amount of electrical energy, approximately 4% in the form of sensible heat, to the surrounding bulk liquid. Rate constants associated with plasma initiated oxidation, interphase mass transfer and photolysis were determined using a combination of nonlinear least squares analysis and MATLAB® optimization techniques for each species. The rate constants developed for the DMPR, in conjunction with a species mass balance on a prototype tubular high-density plasma reactor, have been applied to determine the removal rates of MTBE and BTEX when operating in batch and continuous flow configurations. The dependence of contaminant concentration on parameters such as treatment time, the number of pin electrodes, electrode gap and volumetric flow rate has been determined. It was found that, under various design specifications and operating conditions, the tubular high-density plasma reactor may be an effective tool for the removal of volatile organic compounds from aqueous solutions.
Keywords: chemical engineering; environmental engineering